2021
DOI: 10.1108/bpmj-08-2021-0500
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic relationship of knowledge management processes and project success: modeling the mediating role of knowledge worker satisfaction

Abstract: PurposeConstructed upon a knowledge-based view, the purpose of this paper aims to empirically examine the entrepreneurial leadership impact as knowledge management enabler on knowledge management processes and knowledge management processes on project success. The study further ascertains the mediating role of knowledge worker satisfaction among knowledge management processes and project success.Design/methodology/approachUsing the data collected from 302 project workers from the software industry, China. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 106 publications
(206 reference statements)
0
17
1
Order By: Relevance
“…For the first time, our study attempts to experimentally examine the impact of social dynamics on absorptive capacity and tacit knowledge sharing for project performance. This study challenges the presumptions of earlier research that social dynamics are a societal disadvantage that prevents innovative thinking or managerial endeavors (Shahzadi et al. , 2021).…”
Section: Discussioncontrasting
confidence: 69%
“…For the first time, our study attempts to experimentally examine the impact of social dynamics on absorptive capacity and tacit knowledge sharing for project performance. This study challenges the presumptions of earlier research that social dynamics are a societal disadvantage that prevents innovative thinking or managerial endeavors (Shahzadi et al. , 2021).…”
Section: Discussioncontrasting
confidence: 69%
“…Additionally, SD has a positive effect on GI as well due to its environmental dimension. Also, FI plays an important role in corporate sustainability because the new technology and KM processes provide more versatility and improved efficiency ( Gul et al, 2021d ; Shahzadi et al, 2021 ). In addition to reducing energy demand, preventing emissions, recycling waste, and controlling the environment, advanced technologies are used to continue to enhance development.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Green technologies would increase environmental sustainability while also assisting enterprises in gaining a competitive advantage (Tu and Wu, 2021 ). The value of KMP has long been recognized, and past research has found it to be an important aspect to consider when examining organizational performance, especially knowledge-based innovation (Shahzadi et al, 2021 ). Therefore, we resolved these hypotheses to analyze the relationship between KM practices on environmental awareness and green technology usage.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%